2020
DOI: 10.1186/s12876-020-01297-w
|View full text |Cite
|
Sign up to set email alerts
|

Probiotics use for antibiotic-associated diarrhea: a pragmatic participatory evaluation in nursing homes

Abstract: Background: Antibiotic-associated diarrhea (AAD) occurs in 2-25% of nursing home residents, which may lead to dehydration, malnutrition, severe complications and hospitalizations. Research shows that probiotics can be effective and safe in reducing AAD. However, probiotics are not routinely used in Dutch nursing homes. The objectives of this evaluation were to develop a procedure for the implementation of probiotics to prevent AAD in nursing homes, to evaluate effects on AAD occurrence, and to evaluate the imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 22 publications
0
17
0
Order By: Relevance
“…Probiotics are also indicated to reduce or prevent diarrhea associated with antibiotics and infections by Clostridium difficile, common in hospitalized patients [117,118] and the elderly [119]. In children, its effectiveness in preventing antibiotic-associated diarrhea [120] and in treatment for acute gastroenteritis has not been confirmed, despite reducing the duration of hospitalization [121].…”
Section: Prevention and Treatment Of Infection With Probioticsmentioning
confidence: 99%
“…Probiotics are also indicated to reduce or prevent diarrhea associated with antibiotics and infections by Clostridium difficile, common in hospitalized patients [117,118] and the elderly [119]. In children, its effectiveness in preventing antibiotic-associated diarrhea [120] and in treatment for acute gastroenteritis has not been confirmed, despite reducing the duration of hospitalization [121].…”
Section: Prevention and Treatment Of Infection With Probioticsmentioning
confidence: 99%
“…Studied in antibiotic-associated diarrhoea (Hell et al, 2013;Koning, 2010;Koning et al, 2008;Lang, 2010;Van Wietmarschen et al, 2020) inflammatory bowel disease (Hemert et al, 2013;Lutgendorff, 2009;Mulder, 2008;Persborn et al, 2013;Van der Waal et al, 2019) Constipation (Bekkali et al, 2007;De Milliano et al, 2012) gastrointestinal complaints (Grossenbacher et al, 2016) 1 With the application of new molecular identification techniques (including whole genome sequencing), the declaration of bacterial strains of Ecologic Relief has been updated compared to previous publications. It has been confirmed that the probiotic formulation has always contained these seven strains, and has not been changed in ratio or cfu count since it has been (commercially) available.…”
Section: Data and Analysesmentioning
confidence: 99%
“…Ninety-three residents provided data on 167 episodes of antibiotics use, of which 84 episodes included supplementation with probiotics and of which 83 episodes did not include probiotics supplementation. The number of episodes with AAD when using probiotics was significantly lower than when no probiotics were used (20% vs. 36%; p = 0.022, Chi-square) [ 62 ].…”
Section: Clinical Efficacy Of a Probiotic Productmentioning
confidence: 99%